Enhancing Multiplication Skills: The Way Modeling Method and Mathchess Games in Educational Practice - Pujiastuti, Lise; Wahyudi, Mochamad (International Journal of Enterprise Modelling, 2023)
This research delves into the exploration of an innovative educational approach aiming to enhance multiplication skills among students. The study investigates the combined efficacy of the Way Modeling Method, utilizing visual representations, and Mathchess games, a gamified learning approach, in improving multiplication proficiency. Through a quasi-experimental design involving a control and experimental group, elementary school students aged 8 to 10 were exposed to either traditional instruction or the combined intervention. Pre-tests and post-tests were administered to measure changes in multiplication skills, accompanied by qualitative assessments through participant feedback and observations. The results unveiled significant improvements in the experimental group, indicating a substantial enhancement in accuracy, comprehension, engagement, and confidence in solving multiplication problems. Comparative analysis between groups highlighted the distinct effectiveness of the combined methodology, aligning with cognitive learning theories and emphasizing the potential for dynamic and interactive pedagogical approaches in fostering mathematical skills. These findings present implications for educational practice, advocating for the integration of diverse teaching methodologies catering to varied learning styles. Furthermore, they pave the way for future research in optimizing these approaches and exploring their broader applications in mathematical education.